Creative Problem Solving According to Problem Types Based on Block Type EPL - Won Yi, Do; Ha Song, Eun; Ri Kim, Ju; Mi So, In (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this Paper, one of the tools in the EPL, Scratch is classifying problem solving ability into four problem types and evaluates them by using them.Methods/Statistical analysis: In this paper, we conducted a programming lesson using Scratch EPL for our students. Subjects are irrelevant to grade and major. Based on EPL based block programming, we designed 4-problem types and applied them to COS as a way to evaluate creative thinking and problem solving abilities. The scores according to the problem types were analyzed for each major series.Findings: The target students were divided into four groups based on their major - engineering, social science, the humanities, and science. The problem solving abilities of each major student were tested according to the type of problem they were given.The Type allows only the block to be addressed as suggested, and the CA Type changes the contents within the block according to the instructions. The C-Type allows the free use of blocks to add blocks or modify existing blocks, and the SA Type directs the order of existing blocks. The scores of students majoring in engineering, natural sciences, social sciences, and humanities were analyzed for the types of problems that changed the blocks.Improvements/Applications: The ability to solve and implement the problem was found to be higher in the natural sciences than in the majors and male in the sexes.Â